Současná podoba výuky flétny v ZUŠ - Paterová, Martina (Univerzita Karlova, Pedagogická fakulta, 2022)
The bachelor's thesis focuses on the current form of teaching the flute in basic art schools. The first chapter introduces six selected methodologies and methodological-textbooks from the Czech and foreign environment. It focuses on the views of various authors on issues related to breath, proof, position while playing, holding the instrument and the use of tone. The second chapter is composed of an analysis of the answers of respondents who participated in the questionnaire survey. Based on the answers of the respondents, it was found that the flute is taught in primary music schools by qualified teachers who do not teach only according to one methodology, but combine several approaches at once. Aspects of the game, such as breath, posture, and instrument holding, are the most relevant. They work mostly with their students on the interpretation of recital compositions and choose classical, piano tutoring. More than half of the respondents perceive the current form of teaching as progressive, and some of them themselves propose changes that would contribute to the quality of teaching. Bakalářská práce se zaměřuje na současnou podobu výuky příčné flétny v základních uměleckých školách. První kapitola blíže seznamuje se šesti vybranými metodikami a metodiko-učebnicemi z českého i zahraničního prostředí. Zaměřuje se na to, jaké názory mají různí autoři na otázky týkající se dechu, nátisku, postoje při hře, držení nástroje a nasazení tónu. Druhá kapitola je sestavena z analýzy odpovědí respondentů, kteří se zúčastnili dotazníkového šetření. Na základě odpovědí respondentů bylo zjištěno, že flétnu vyučují v ZUŠ kvalifikovaní pedagogové, kteří nevyučují pouze podle jedné metodiky, ale kombinují více přístupů najednou. Nejvíce se zabývají aspekty hry jako je dech, postoj a držení nástroje. Se svými žáky pracují nejvíce na interpretaci přednesových skladeb a volí k tomu klasickou, klavírní korepetici. Jako pokrokovou vnímá současnou podobu výuky více než polovina respondentů a někteří z nich sami navrhují změny, které ...